Physical performance, anthropometric measurements and basic skills of football players in Karbala, Iraq - Abdulameer, Mothna Mohammed (2016)
This study aimed to identify and determine the most related tests to measure the physical performance, anthropometric measurements, and basic skills in the first division football club in Karbala, Iraq. In addition, this study aimed to identify the level of selected physical performance, anthropometric measurements and basic skills and compare the mean difference among the study variables for football players based on the three playing positions. Descriptive method was used for its suitability to the study objectives by testing 92 football players (mean age M= 20.8, SD = 1.83, mean height M= 172.75, SD = 7.28, mean body weight M= 65.26, SD = 7.01). Questionnaires were adapted from previous research to identify more related variables and tests. Later, experts’ opinions were used to select the suitable tests for physical performance, anthropometric measurements, and basic skills. The test that has score above 70% was chosen as the test to measure the selected variables. All of the four clubs in Karbala, Iraq were invited to participate in this study. The players were divided based on the three playing positions (defense, midfield and offensive). The results showed that Shuttle test 40x5, 30 m sprint, passing with wall, Nelson speed of movement, sit down and stand up, vertical jump and dribbling 25 m are the selected tests for physical performance in football. For anthropometric measurements, total weight, total length, lower limb length, and chest circumference are selected, whereas passing accuracy, receiving ball, ziz-zag dribbling, competitor evasion, heading the ball and accuracy test for shooting are the selected tests for basic skills in football. The results based on playing positions showed that the defense group has the highest mean score for all the tests. The tests are passing with the wall for physical performance, width chest for anthropometric measurements and dribbling 25m between cones for basic skills. However, Welch test only showed significant results for Nelson speed of movement (Welch statistic = 3.437, p <0.05) and dribbling 25m between cones (Welch statistic = 7.358, p <0 .05) for physical performance, total length (Welch statistic = 4.475, p <0.05) and chest circumference (Welch statistic = 3.510, p <0.05) for anthropometric measurements, and passing (Welch statistic = 9.921, p <0.05) and controlling (Welch statistic = 4.896, p <0.05) for basic skills among groups. Selected tests can be used as a practical way for the coaches, not only in Karbala but also in other parts of Iraq and other countries to select the players and to monitor and compare their performance with themselves and other players.